Climate's role in Earth's shifting spheres. Issue 4 (26th October 2020) - Robertson, Robin
Abstract : Purpose: This paper aims to present the physics of climate and climate change in an accessible manner to the layman in the context of shifting spheres. Design/methodology/approach: This paper presents the physics of climate and climate change in an accessible manner to the layman in the context of shifting spheres. This is a viewpoint and more of a literature review than new findings. Findings: Earth's climate is changing due to man's influence. Social implications: Climate change will be a major factor in the future of our society. Originality/value: The text is original. The information is not. There is recent information in this article. The author even updated things during the review process. The science is always improving.